Patent blue and air as an alternative for resection of nonpalpable breast lesions: a case series - Vieira, Sabas Carlos; Alves, Viviane Carvalho; Oliveira, Tayná Cristinne Barros de; Ibiapina, Jacira Oliveira; Soares, Emmyle Cristyne Alves; Crisanto, Marcus Luciano Lopes de Paiva (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Use of mammography for breast cancer screening has resulted in a significantly increased number of patients with nonpalpable radiological findings that need histopathological study for better management. The present study evaluated an alternative to excision of nonpalpable breast lesions, using injection of patent blue (CAS 3536-49-0) dye and air. DESIGN AND SETTING: Cohort study of 64 consecutive patients at a private clinic in the city of Teresina (Piauí), between January 2009 and December 2010. METHODS: The patients had received mammographic diagnoses of nonpalpable breast lesions classified as BI-RADS 3, 4 and 5, with indication of histopathological study. They underwent stereotaxy and/or ultrasound-guided injection of patent blue, for marking and subsequent excision of the lesion. RESULTS: The patients’ mean age was 47.7 years. Nodes accounted for 53.1% of the breast abnormalities; microcalcifications, 37.5%; and complex cysts, 9.4%. In 89.1% of cases, the lesions were BI-RADS 4; 7.8% were BI-RADS 5 and 3.1% were BI-RADS 3. The histopathological findings were benign in 70.3% of the cases; atypical hyperplasia, 9.4%; and malignant, 20.3%. Among the malignant cases, 53.8% were carcinoma in situ and 46.2%, invasive carcinoma. The percentage of malignancy was 0% in BI-RADS 3 lesions; 14.3% in BI-RADS 4 and 100% in BI-RADS 5. In the cases of malignancy, the margins were clear in 92.3%. Reoperation to widen the margins was required in one patient. CONCLUSION: Excision of nonpalpable breast lesions marked with patent blue and air was possible in all cases.